High performance pipelined FPGA implementation of the SHA-3 hash algorithm - Ioannou, Lenos; Michail, Harris; Voyiatzis, Artemios G. (My University, 2015)
The SHA-3 cryptographic hash algorithm is standardized in FIPS 202. We present a pipelined hardware architecture supporting all the four SHA-3 modes of operation and a high-performance implementation for FPGA devices that can support both multi-block and multi-message processing. Experimental results on different FPGA devices validate that the proposed design achieves significant throughput improvements compared to the available literature.
Keywords: FPGA; Hash algorithm; High performance; Pipeline; SHA-3